Effect of single Vs double insemination on farrowing rate and litter size in sow - KADIRVEL, G; DAS, ANUBRATA; NASKAR, S; HASIN, DILRUBA; BUJARBARUAH, K M (The Indian Journal of Animal Reproduction, 2023)
Semen was collected from Hampshire boar by gloved-hand technique twice weekly and extended in Beltsville Thawing Solution (BTS) at the rate of I :4 to I: 5 depending upon concentration. Seventy to eighty ml of extended semen (2-3 billion sperm) was packed in the sachet and preserved at l 7°C. In group I (No = 25), sows were given single insemination, while Group II (No = 27) received double insemination during standing estrus at 24 h interval. Sows in group III (No =20) were allowed for natural service (NS) and served as control. The farrowing rate with single insemination was 68% with an average litter size of 7.6±0.3. Whereas in double insemination group, the farrowing rate was 77% with an average litter size of 9.2±0.2. There was significant (P 0.05) difference between single and double insemination groups on the farrowing rate and litter size. Similarly, the farrowing rate (80%) and litter size (9.4±0.2) in NS group were significantly (P 0.05) higher than that in single insemination group. However, there was no significant difference between double insemination group and NS group on farrowing rate and litter size . It was concluded that inseminating estrus sows twice at 24h interval would favour the farrowing rate and litter size, which is more or less equal to single natural mating.